Study of Aspergillus niger resistance to low concentration preservatives in media with essential oils - Berezovska, M.Y.; Andrianova, T.V.; Seden, I.A. (Problems of Environmental Biotechnology, 2023)
The aim of the research was to analyze the inhibitory action of compound mixtures that consisted from weakened preservatives and essential oils on fungi, especially on A. niger. It was hypothesized that the cell wall structure of A. niger can contribute to the fungus resistance to a treatment based on a combination of weakened preservatives when combined with essential oils.